EVALUASI KONDISI RESERVOIR BERDASARKAN MONITORING GEOKIMIA FLUIDA PADA SUMUR PRODUKSI AGS-2 DAN AGS-8 LAPANGAN PANAS BUMI PATUHA, JAWA BARAT - Ari Gunawan Sentosa; Agus Didit Haryanto; Dewi Gentana; Hendy Sujarmaitanto (PPSDM Geominerba, 2022)
Patuha Geothermal Field is a vapor-dominated fluid system that mostly produces dry steam which associated with Quaternary Patuha Volcano. This field is located in Bandung Regency, West Java and has been exploited since 2014. This exploitation can cause changes in fluid characteristics of reservoir therefore the monitoring activity is carried out to identify these changes. This study uses fluid chemistry and tracer flow test data from two production wells, AGS-2 and AGS-8. The method used is a geochemical analysis of geothermal fluids. The results showed that the fluid from these wells are still influenced by magmatic volatiles which AGS-8 shows higher intensity than AGS-2. The concentration of non-condensable gases (NCG) has decreased since the start of exploitation, indicates that the boiling process is still ongoing in reservoir. AGS-2 well has meteoric water influx which causes the low value of dryness and enthalpy ​​also high potential of silica scaling compared to AGS-8.